Multi objective optimisation of abrasive water jet parameters for titanium alloy using Box–Behnken response surface methodology - Abdul Halim, Nurul Hayati; Tharazi, Izdihar; Abdullah, Abdul Hakim; Mohd Salleh, Farrahshaida; Morni, Mohamad Firhan; Marzuki, Afeeqa Puteri; Khalit, Muhammad Ilham (UiTM Press, 2025)
Titanium alloy is widely used in aerospace, military, and biomedical industries due to its high tensile strength and toughness, even at extreme temperatures. However, its poor machinability presents challenges for conventional cutting methods. Abrasive water jet machining (AWJM) is widely utilised for processing such hard-to-machine materials. This study aims to optimise critical AWJM parameters, including abrasive flow rate (0.286 kg/min - 0.318 kg/min), traverse speed (2000 mm/min - 4000 mm/min), and stand-off distance (5 mm - 15 mm), for machining titanium alloy using Response Surface Methodology (RSM). A total of 17 experimental runs were conducted, and analysis of variance (ANOVA) was applied to evaluate the influence of the selected parameters on kerf width, surface roughness, and material removal rate (MRR). Scanning electron microscopy (SEM) was also employed to examine the surface defect pattern and microstructural characteristics on the machined surface. The results show that stand-off distance and traverse speed were the most significant factors affecting all three responses, with optimal values of 5 mm and 3000 mm/min, respectively. Increasing the stand-off distance led to higher values for all responses, while an increase in traverse speed produced the opposite trend. The abrasive flow rate was the least influential, with an optimal value of 0.318 kg/min. SEM analysis revealed surface defects such as garnet embedment, ploughing, and grooves under non-optimised conditions. The optimised parameters obtained can improve the machining quality and serve as a useful reference for future research and industrial applications.